Postoperative Nursing Care of Patients after Hysterectomy - Madekša, Renata; Stundžienė, Rasa (Slauga. Mokslas ir praktika, 2020)
The aim of the research work: to find out about the patients’ post- operative period of nursing after abdominal and vaginal hysterectomy.Materials and methods. The research was done at Vilnius University Hospital Santaros Clinics in gynecology section. The study involved 56 patients after hysterectomy, of which 24 were after abdominal and 32 after vaginal hysterectomy. All the patients were supervised twice (early and late postoperative period). The research was done from December 2016 till March 2017. There were used 3 methods to accomplish the study: analysis of the medical documents, protocol of observation (which was prepared by the author) and the questionnaire survey (which was prepared by the author). Data analysis was performed using statistical analysis SPSS 19.0 for Windows and Microsoft Office Excel 2010 programs.Results. The average age of patients was 59.39 ± 10.2. The majority of them had gain high non – University education (n = 21; 37.5 proc.). The most common reasons for having a hysterectomy were pelvic organ prolapse (n = 2 9; 51.8 proc.) and uterine myoma (n = 16; 28.5 proc.). It was found that in the early postoperative period the patients after vaginal hysterectomy were often suffering from bloody vaginal discharge (p = 0.002) while the patients after abdominal hysterectomy were more often complaining about the movement problems (p=0.002).Conclusions. 1. It was found that the main problems of patients after hysterectomy in the early postoperative period were pain, weakness and inactiveness. In addition, the main problems remained pain and the lack of activity at the late period and regardless of the surgery type. 2. It was investigated that after abdominal and also after vaginal hysterectomy the most often used nursing actions were: the assessment of pain intensity and its relief, granting a comfortable body position, rest periods and alternative activities assurance, insuring quiet invironment, conferment of bladder catheter care and the administration of medicaments. 3. It was found that, the most of the patients were satisfied with the nursing care, which was provided in postoperative period and it was evaluated greatly as well.
Keywords: vaginal hysterectomy; abdominal hysterectomy; postoperative nursing; nursing problems; patients opinion